RESPONSIBILITIES OF THE REPAIR STUDENT IN MUSEUMS - Abdudaeva Sadokat (Research Parks Publishing LLC, 2020)
This article provides information to museum repairmen on all methods of working in the museum, including the work carried out in the museum stock, repair and conservation.